2009
DOI: 10.1007/s10611-009-9210-4
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in police decision-making with youth: an application of Black’s theory of law

Abstract: Prior research suggests that police officers may use more than one style of law (therapeutic, conciliatory, compensatory, penal) and that the quantity of law applied may also vary within an encounter in order to maintain order. The implication is that police decision-making varies, and is, to some extent, case dependent. The research objective is to investigate the extent to which principles from Black's (1976) theory of law are applicable to police decision-making with apprehended youth in Canada. The findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…In particular, juvenile suspects were generally handled in an informal manner or, if an arrest was made, it was because the parent or caregiver requested one. This is similar to Schulenberg's (2010) finding that the majority of officers will consider informal action when encountering a juvenile in the field. In particular, over 90% of officers reported using informal warnings or involving the parents to resolve the encounter (Schulenberg, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…In particular, juvenile suspects were generally handled in an informal manner or, if an arrest was made, it was because the parent or caregiver requested one. This is similar to Schulenberg's (2010) finding that the majority of officers will consider informal action when encountering a juvenile in the field. In particular, over 90% of officers reported using informal warnings or involving the parents to resolve the encounter (Schulenberg, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…age, race and demeanour) (Gaines & Kappeler, 2011). Policing research has given increased attention to the values, skills and experience police bring to their work (Schulenberg, 2010), and some recent work has investigated values such as ‘blameworthiness’ in relation to discretionary decision-making with adults (Ishoy & Dabney, 2018). However, there has been less attention to investigation of the values that inform decision-making with young people (see Richards, 2019; Richards et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There is increased recognition in criminological theory of the importance of agency in the policing role – that police are human and bring values, experiences and skills to situations (Schulenberg, 2010). International research has demonstrated a strong link between individual police views about young people and their discretionary decision-making (Brunson, 2007; Solis, Portillos, & Brunson, 2009; Vera Sanchez & Adams, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to adults, crimes involving young people are interpreted differently by police (Carr, Hudson, Hanks, & Hunt, 2008; Parker & Sarre, 2008; Schulenberg, 2010; Schulenberg & Warren, 2009). Allen (2005) argues that delinquent behavior committed by young people is perceived as more serious than similar behavior carried out by an adult.…”
Section: Juvenile Delinquents and Police Decision-makingmentioning
confidence: 99%